Indikator Makroekonomi dan Pengaruhnya Terhadap Indeks Saham Syariah di Indonesia - Heri Sudarsono (Faculty of Economic and Business, 2018)
This study aimed to analyze the influence of variables of money supply (M2), constumer price index (CPI), exchange rate (ER), BI Rate (BIRATE), Sertifikat Bank Indonesia Syariah (SBIS) with Shari'ah Indonesia Stock Index (ISSI). To see that effect will be made by the tests in stages Vector Autoregression. The data used in this research is secondary data during the period January 2012 until December 2016. The finding in long run shows that ISSI is positively significantly affected by CPI and it is negatively significantly affected by M2, ER and BIRATE. Granger-Causality test resulth shows that there are causality between CPI with BIRATE and CPI with SBIS, but there are three undirectional relationship which includes ISSI to ER, M2 to BIRATE and SBIS to BIRATE.DOI: 10.15408/ess.v8i2.7219